The Gradient of a Solution of the Poisson Equation in the Unit Ball and Related Operators. Issue 3 (1st September 2017) - Kalaj, David; Vujadinovic, Djordjije
Abstract: In this paper we determine the L^1→ L^1 and L^∞ → L^∞ norms of an integral operator N related to the gradient of the solution of Poisson equation in the unit ball with vanishing boundary data in sense of distributions.